The Effect of Potassium Dosage and Branch-Pruning on the Growth and Yield of Butternut Squash (Cucurbita moschata Durch) - F. Deru Dewanti; Nora Augustien; Nova Triani; Nurul Islam Fi Holki; Sukarjati (Postgraduate, University of Mataram, 2024)
Butternut squash (C. moschata) is a honey squash plant (Cucurbita moschata Durch) which is an introduced plant from the lowlands of South America and has adapted to Indonesia. The research was carried out in the planting area of Kampung Labu Madu, Toyoresmi Village, Ngasem District, Kediri Regency from January to June 2021. Potassium is among major nutrients needed by plants in their growth and development. Potassium fertilization can help plants improve the regulation of photosynthetic mechanisms, carbohydrate translocation, protein synthesis This research was a two-factor factorial experiment prepared using a Split Plot Design. The first factor (main plot) was the branch pruning (P) treatment which consisted of 2 levels and the second factor (subplot) was the dose of KCl (K) fertilizer which consisted of 4 levels. The results of the research showed that there was a real influence in the treatment without pruning on the parameters of the number of male flowers and on the parameter of fruit weight with the best treatment being pruning, whereas for the treatment the dose of KCl fertilizer had a real effect on the parameters.